2016
DOI: 10.1186/s12883-016-0555-x
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese female Morvan patient with LGI1 and CASPR2 antibodies: a case report

Abstract: BackgroundMorvan syndrome is a rare disorder characterized by the combination of peripheral nerve hyperexcitability, encephalopathy and dysautonomia with marked insomnia. It was reported to have association to antibodies to voltage-gated potassium channels including contactin associated protein-like 2 antibodies (CASPR2-Ab) and leucine-rich glioma inactivated protein 1 antibodies (LGI1-Ab). LGI1-Ab was reported to associate with seizures, amnesia, confusion, hyponatraemia and a good prognosis, while CASPR2-Ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…12 However, patients with relatively mild clinical symptoms exhibit lower frequencies and discontinuous discharge modes and can thus even show normal EMG results. 13 Afterdischarges are continuous discharges after stimulation of action potentials and can promote hyperactivity of motor nerve membranes, thus serving as sensitive markers when hyperexcitability levels are low. Additionally, we found that after-discharges are more common in the tibial nerve, which is consistent with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, patients with relatively mild clinical symptoms exhibit lower frequencies and discontinuous discharge modes and can thus even show normal EMG results. 13 Afterdischarges are continuous discharges after stimulation of action potentials and can promote hyperactivity of motor nerve membranes, thus serving as sensitive markers when hyperexcitability levels are low. Additionally, we found that after-discharges are more common in the tibial nerve, which is consistent with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Petit-Pedrol et al (2014) recently reported five cases of anti-GABA A R and anti-GAD65 antibodies co-occurring in CSF and serum [ 17 ], and a single case report of a female with encephalitis was found to harbor anti-GABA A R and anti-GAD65 antibodies in CSF and serum [ 184 ]. Other double antibody positivity combinations that have been identified are anti-NMDAR and anti-GAD antibodies [ 185 ], anti-NMDAR and anti-D2R [ 165 , 186 ], anti-GABA B R and anti-Hu [ 187 ], and anti-Caspr2 and anti-Lgi1 in a patient with Morvan syndrome [ 188 ]. Recently, patients positive for anti-MOG and anti-NMDAR antibodies were reported [ 189 ], and later on, double antibody positivity for anti-NMDAR and anti-GlyR and anti-MOG and anti-GlyR antibodies were also shown in two patients [ 190 ].…”
Section: Potential Mechanisms Of Double Autoantibody Positivitymentioning
confidence: 99%
“…The mechanism(s) by which CASPR2 and LGI1 antibody cause insomnia remain(s) unclear, though it was suggested that these proteins, located mainly in the neocortex and limbic areas, may be involved in the regulation of sleep need or efficiency via modulation of potassium channels. Only few reports have highlighted the reversal of insomnia in autoimmune encephalitis upon immune-modulatory therapy [4, 9, 10], as in the present case. Our patient demonstrated a major benefit from immune-modulatory therapy in terms of insomnia, as demonstrated by both clinical and polysomnographic evaluations.…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, a few MoS cases with both LGI1 and CASPR2 antibodies and an incomplete clinical picture have been previously reported. However, these patients have displayed either severe PNH features (e.g., cramps, fasciculations, neuromyotonic discharges) without encephalopathy or prominent encephalopathy features (e.g., hallucination, confusion, amnesia, or seizures) with mild (e.g., myokymia only) or no PNH findings [4, 5, 6], while our patient showed minimal features of both PNH and encephalopathy findings.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation